The Potential Relationship Between HIF-1α and Amino Acid Metabolism After Hypoxic Ischemia and Dual Effects on Neurons - Li, Kexin; Zheng, Yang; Wang, Xiaoming (Frontiers in Neuroscience, 2021)
Hypoxia inducible factor (HIF) is one of the major transcription factors through which cells and tissues adapt to hypoxic-ischemic injury. However, the specific mechanism by which HIF regulates amino acid metabolism and its effect on neurons during hypoxic ischemia (HI) have remained unclear. This study analyzed the changes in cerebral metabolism of amino acids after HI by using 1H-MRS and investigated the relationship between the changes in cerebral metabolism of amino acids and HIF-1α as well as the potential effects on neurons. Newborn pigs were used as an HI model in this study. Twenty-eight newborn Yorkshire pigs (male, 1.0–1.5 kg) aged 3–5 days were selected and randomly divided into experimental groups tested at 0–2 h (n=4), 2–6 h (n=4), 6–12 h (n=4), 12–24 h (n=4), 24–48 h (n=4), and 48–72 h (n=4) after HI, and a control group (n=4). After the modeling was completed, 1H-MRS imaging was conducted, followed by immunohistochemical staining of HIF-1α, NeuN, and doublecortin (DCX), and immunofluorescence of glutamic oxaloacetic transaminase (GOT)-1, GOT2, glutathione synthase (GS), glutamate-cysteine ligase catalytic subunit (GCLC), and glutamate-cysteine ligase modifier subunit (GCLM) in brain tissues. The expression of HIF-1α exhibited two increases after HI injury. The first time was opposite to the trends of change of GOT2, aspartic acid, and the number of neurons, while the second was consistent with these trends, suggesting that HIF-1α may have a two-way induction effect on neurons by regulating GOT2 after HI. HIF-1α was closely related to GCLM expression, and GSH level was correlated with the number of hippocampal neurons, indicating that HIF-1α may regulate GCLM to promote GSH synthesis and additionally play a neuroprotective role.